(untitled) (Letras & Letras, 2007)
ABSTRACT: This article deals with the ’problem’ of the death in Alceste, a euripidian tragedy. It is discussed its fine ambiguity, its worth for present time and its meaning. Particular attention is called upon the singularity of the genre of the play. Our reading flows from the idea that it is impossible to establish the play’s genre as tragic, tragicomic or satirical. We also investigate the presence of laugh in this tragedy.